2019
DOI: 10.1186/s12889-019-6901-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the promising neighbourhoods community program to reduce health inequalities in youth: a protocol of a mixed-methods study

Abstract: Background Reducing socioeconomic health inequalities among youth is a major challenge for governments around the world and reports on successful attempts are scarce. Socioecological and integral approaches with collaborative partnerships and community engagement are recommended but knowledge about the effectiveness and effective and ineffective elements is limited. The Promising Neighbourhoods program employs such an approach aiming to reduce socioeconomic inequalities in health, safety and talen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…We already know that being in high-risk neighborhoods and interacting with high-risk peers are major risk factors for behavioral problems and poor outcomes [ 93 ]. As the environment is modifiable by policy, there is a need to address segregation and environmental risk in predominantly NHB schools and neighborhoods [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…We already know that being in high-risk neighborhoods and interacting with high-risk peers are major risk factors for behavioral problems and poor outcomes [ 93 ]. As the environment is modifiable by policy, there is a need to address segregation and environmental risk in predominantly NHB schools and neighborhoods [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…33 An important part of this programme is collaborative planning of preventive measures and interventions at the neighbourhood level focusing on an increased use of evidence-based preventive interventions especially on the domain of mental health promotion. 34 Furthermore, the community-based support teams may have increased the availability, accessibility and acceptability for primary youth care, which may have resulted in a reduced gap between those in need for care and actually receiving care. Earlier studies found improved access to care as a result of integrated forms of care 35 36 and colocation of social workers.…”
Section: Discussionmentioning
confidence: 99%
“…EPODE demands substantial investments in terms of money, time, and effort from all stakeholders, which makes their acclaim remarkable given the absence of systematic evidence for the approach’s effectiveness. Multiple study protocols have been published [ 13 15 ], but only four studies describe the adaptations’ effectiveness. An evaluation of the Belgian adaptation showed a trend towards a decrease in overweight ( p = .05), and overweight + obesity ( p = .06) in pilot towns compared to the general population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%